Perception of long-distance romantic relationship among FCI students in University Tunku Abdul Rahaman (UTAR), Sungai Long - Goh, Vi Vien (2024)
Long-distance romantic relationships (LDRRs) were often seen as challenging and unfeasible before the advent of the Internet. Communication was limited to the traditional medium, such as expensive phone calls, letters, and occasional visits, which made it difficult to maintain a relationship. However, with the emergence of new media, communication has become simpler and more accessible, making it easier for people to maintain close connections with their partners, even when separated by distance. To maintain a successful LDRR, it is essential to understand how male and female students perceive such relationships. Unfortunately, there are limited studies on gender perceptions amongst UTAR students and their acceptance towards LDRRs. Therefore, this study aims to find out if the education level significantly correlates with the level of acceptance towards long-distance romantic relationships amongst students and to find out the different perceptions of male and female students about long-distance romantic relationships. The data was collected through an online survey with 109 male and female students in UTAR Sungai Long, and a descriptive analysis method was used to analyse the data collected. The findings discovered that male and female participants have different perceptions on LDRRs. Nonetheless, both genders acknowledge that communication and trust are vital components of maintaining LDRRs.